A Novel Method for Efficient Micropropagation of Radermachera xylocarpa (Roxb.) K. Schum., a Rare Medicinally Important Forest Species (Plant Tissue Culture and Biotechnology, 2013)
Radermachera xylocarpa (Roxb.) K. Schum. is a rare indigenous forest tree species which is utilized for its wood and medicinal properties. Due to its overexploitation and specific habitat requirements the species is restricted to limited areas. In vitro mass propagation of tree species faces various challenges and no such efforts have yet been taken in propagation of this useful plant using these methods.  In order to overcome the hurdles and understanding an urgent need of its conservation and mass propagation present authors attempt to develop a simple effective tissue culture protocol for regeneration of R. xylocarpa. Nodal explants were cultured on MS supplemented with various concentrations of cytokinins and auxins.  Among different cytokinins, maximum bud induction and proliferation was obtained in media supplemented with Kn along with IBA and for effective root induction which is tough to obtain in tree species, 100% rooting was achieved in cultures with increasing concentrations of IBA. Field survival is a major challenge with regenerated plants of forest tree species. We report here for the first time 100% survival of plants in soil by carefully standardizing the period of hardening and acclimatization procedures. A novel and effective in vitro regeneration protocol of R. xylocarpa has been successfully standardized which can be adopted for large scale propagation, reforestation and conservation of rare Radermachera xylocarpa of medicinal importance.Plant Tissue Cult. & Biotech. 23(1): 21?29, 2013 (June)DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15556